Strategi Penguatan Pendidikan Karakter Islam - Abd Wahid (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2019)
The essence of Islamic education is character education. Islam views and teaches morality is more important than the glory of science. Islamic education asserts that virtue values are the content of Islamic education. The content of Islamic education is character or value. Value education emphasizes the importance of the process of awareness that humans need that value to improve their spiritual quality and life. Strengthening is done by various strategies such as: integration in the learning process, habituation, exemplary, joint movements and become a priority scale for the formation of mentality and human resources in Indonesia in the future. The emphasis of learning should be done as a process of directing and developing individuals in the process of realizing the importance of character and values in shaping their self and spiritual qualities.